Thinking of Harm, Surveillance and Corporate Responsibility in Digital Criminology - Jiachen Xu (Studies in Law and Justice, 2025)
This paper explores how harm, control, and responsibility appear in the digital age, using the 2023 Latitude Financial data breach and technology-facilitated abuse cases as examples. The study applies digital criminology and surveillance theory to understand the hidden and complex nature of modern cybercrime. First, it discusses how hackers use technical methods to attack companies indirectly, and how poor communication after a breach can increase the harm to users. Then, it shows how surveillance tools are also used in private settings, such as domestic violence, to control victims. The paper finds that harm in the digital world is often invisible, long-term, and hard to prevent. It argues that current laws are not enough to deal with these new types of crime. Stronger regulation, better cross-border cooperation, and more attention to surveillance misuse are needed to protect people in digital environments.